Fish communities in small subtropical reservoirs subject to extensive drawdowns, with focus on the biology of Enteromius paludinosus (Peters, 1852) and Clarias gariepinus (Burchell, 1822) - Nhiwatiwa, Tamuka; Maseko, Zolile; Dalu, Tatenda (Ecological research, 2017)
Small reservoirs are characterised by extreme fluctuations in water levels, but how this affects fish communities is not well understood. The aim of the study was to investigate fish communities in two small reservoirs which experience large water level fluctuations over two study years, wet and dry. Six fish species were caught in both reservoirs during the sampling period. The numerically dominant fish species was Enteromius paludinosus in both reservoirs, with Clarias gariepinus contributing the high overall fish biomass. The cyprinids Enteromius lineomaculatus and Enteromius trimaculatus occurred in small numbers, as well as the cichlids Oreochromis mossambicus and Tilapia sparrmanii. Using GLMM, the abundance of both C. gariepinus and E. paludinosus across the two reservoirs was found to be significantly associated with total nitrogen and inorganic nitrogen. C. gariepinus abundances were also associated with water transparency and reactive phosphorus whilst E. paludinosus abundances were associated with ammonia, alkalinity, total dissolved solutes and water depth. E. paludinosus bred mostly during the rainy year. Fish migrations and spawning events were largely triggered by rainfall. Differences between the fish populations in the two reservoirs were small based on fisheries metrics due to the biological attributes of the dominant species, E. paludinosus and C. gariepinus . The shallowness and frequent water level fluctuations in small reservoirs possibly do not allow for specialised habitats to develop, which could lead to high fish species diversity. Their suitability for small-scale fisheries has to be reconsidered as the demand for water for irrigation far outweighs that of the fishery.